1983
DOI: 10.1128/mcb.3.9.1634
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of unstable multidrug cross resistance in Chinese hamster ovary cells with a homogeneously staining region on chromosome 1.

Abstract: An enrichment selection method using repeated pulses of low drug concentration (1 ,ug/ml) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 32 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The presence of double minute chromosomes and homogeneously staining regions in multidrug-resistant human and rodent cells is consistent with this mechanism (1,8,11). More recently, the development of in-gel renaturation techniques by Roninson (19) has allowed the direct visualization of amplified genomic DNA.…”
supporting
confidence: 61%
“…The presence of double minute chromosomes and homogeneously staining regions in multidrug-resistant human and rodent cells is consistent with this mechanism (1,8,11). More recently, the development of in-gel renaturation techniques by Roninson (19) has allowed the direct visualization of amplified genomic DNA.…”
supporting
confidence: 61%
“…It has been suggested that multidrug resistance is due to a decreased intracellular drug accumulation (2,3) caused by alterations of the plasma membrane (4)(5)(6). Multidrug-resistant cells often contain double minute chromosomes or homogeneously staining chromosomal regions, suggesting that gene amplification at least in part underlies multidrug resistance (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Homogeneously staining regions or double minute chromosomes, both known to carry amplified DNA, have been observed in a variety of multidrug-resistant cell lines (3,5,12,29). The degree of amplification, reflected by the size of the homogeneously staining region or the number of double minute chromosomes, can be correlated with the level of P-glycoprotein overproduction (5,29,31).…”
mentioning
confidence: 99%